2018
DOI: 10.1016/j.exer.2018.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Carnosic acid attenuates acrylamide-induced retinal toxicity in zebrafish embryos

Abstract: Acrylamide (ACR) is a water-soluble chemical used widely in industry, which can be formed in tobacco smoke and in starchy foods cooked at high temperatures. ACR is considered to be a neurotoxin, genotoxin and carcinotoxin. Previous studies reported that ACR-exposed workers and experimental animals exhibited visual function defects, although the underlying mechanisms have not been elucidated. In this study, we found that zebrafish embryos exposed to 1 mM and 2 mM ACR showed significantly increased reactive oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This discrepancy might stem from different experimental duration and substance dose regimen as well as the interplay between the toxic and the protective substances. In a study of Albalawi et al [ 36 ] in zebrafish embryos, carnosic acid reduced acrylamide‐induced retinal toxicity. In addition, in contrast to our results, they found that while acrylamide alone decreased Nrf2 levels, carnosic acid cotreated with acrylamide increased Nrf2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might stem from different experimental duration and substance dose regimen as well as the interplay between the toxic and the protective substances. In a study of Albalawi et al [ 36 ] in zebrafish embryos, carnosic acid reduced acrylamide‐induced retinal toxicity. In addition, in contrast to our results, they found that while acrylamide alone decreased Nrf2 levels, carnosic acid cotreated with acrylamide increased Nrf2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of AA on SOD activity in different experimental models has been reported in many previous studies, but the results seem to be inconsistent. The observation result of some studies is that under the administration of AA, SOD enzyme activity was significantly inhibited, which indicates that AA induced redox imbalance and the antioxidant defense system failed to combat the influx of ROS [ 31 , 40 , 41 , 42 ]. In contrast, another part of the study showed that the stimulation of AA increased the activity of SOD, and it is thought to be a compensatory mechanism against oxidative stress [ 3 , 20 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies in rodents and other experimental models have demonstrated that exposure to monomeric ACR to cause carcinogenicity, developmental toxicity, neurotoxicity, and genotoxicity 2 .…”
Section: Ijpsr (2020) Volume 11 Issue 2 (Research Article)mentioning
confidence: 99%